Delignification of Lignocellulosic Content of Sugarcane Bagasse (Saccarum officinarium) with Variations in Size and Pretreatment Time - Yusuf, Andi Asdiana Irma Sari; Abadi, Sakinah Islamiati; Sariwahyuni (Journal of Chemical Process Engineering, 2024)
Sugarcane bagasse (Saccarum officinarium) is a byproduct of the sugar production process and holds potential as a raw material for bioethanol production due to its lignocellulose content. Lignocellulose contains important components such as cellulose, hemicellulose, and lignin. This study focuses on the delignification of sugarcane bagasse (Saccarum officinarium) through a combination of mechanical and autoclave treatments, with variations in particle size and heating time. The goal of this study is to reduce the lignin content and increase the proportion of cellulose and hemicellulose, key components for producing valuable products  for instance bioethanol. In this research, sugarcane bagasse was processed with particle sizes of 60, 70, and 80 mesh, and heated in an autoclave for 30, 45, and 60 minutes. The Chesson-Datta method was used to analyze the lignocellulose content of the bagasse after the delignification process. The results showed that the best outcome was achieved with a particle size of 80 mesh and a heating time of 60 minutes, yielding the lowest lignin content at 14.27%, while cellulose and hemicellulose reached 44.3% and 26.75%, respectively. This indicates that variations in particle size and heating duration significantly affect the effectiveness of the delignification process. Optimizing these two parameters is crucial for increasing cellulose and hemicellulose content while reducing lignin. Further research is expected to develop more effective pretreatment techniques to enhance the efficiency of sugarcane bagasse biomass conversion for industrial applications